Uzbrojenie w świetle źródeł pisanych w Polsce do połowy XIII w. - Szymczak, Jan (Acta Universitatis Lodziensis. Folia Archaeologica, 2001)
In the paper all the written records concerning defensive weapons, protective weapons, horse armament, horse harness and horseman equipment found in the early Mediaeval sources such as chronicles by Gall Anonim, called Gall, and by Master Vincent, known as Kadłubek, and in the oldest hagiographie sources and the annals and several documents drawn up till the year 1250 have been subjected to analyses. Among offensive weapons the main role was played by edge weapon, /side- arms/, a sword particularly, defined as gladius, ensis, mucro, spatha. A dagger occurs as a pugio, but in some sources this word stands for an ordinary knife, that is cuhellus. Shaft weapon is represented by a spear – venahulum. The word lance stands, first of all, for lancea and hasta, but also for cuspis and pilu. Among the head weapon, a battle-axe, along with a pickaxe, are the most commonly mentioned type of weapon. Commonly occurring word securis, i.e. a hatchet, is a term describing both a weapon and a tool. Sporadically the word francisca occurs as a synonym of the word securis. Among shooting weapon occur a bow arcus and a crossbow balista, whereas sagittae, pila, iacula are the terms used for bullets. Among protective weapon a helmet, once described as galea, other times as galimate, and sporadically as cassis, seems to have a leading possition. Warrior’s body was protected with a lorica, most probably meaning a hauberk, although equally well this word may define scale-armour or lamel-armour. The term clipeus was used for a shield, less often also called scutum and pelta. A horse occurring as equus is a frequent quest visitor on the pages of early Mediaeval sources. Different breeds and functions of this animal were expressed by names such as caballus and asturco as well as ambulator, palefridus, emmisarius and dextrarius. Horse bard and horseman equipment did not gain recognition in the eyes of the chroniclers who mention solely a saddle – sella, spurs – calcarium and a bit – frenum. Although the Polish early Mediaeval sources include a rich span of names of weapons, yet they do not allow to identify precisely the types of arms in use. In chronicles literary form predominates over reality, the documentary sources having remained very scarce.